South by Java Head - MacLean, Alistair 1922-1987 (Fontana Collns Sons & Company Ltd, 1958)
Set in the fall of the British stronghold of Singapore to the Japanese Army in February 1942. A mixed collection of soldiers, nurses, fleeing civilians, a small boy, and at least one spy attempt to escape the burning city aboard the Kerry Dancer, a battered freighter manned by a disreputable captain and crew. When the Kerry Dancer is crippled by Japanese war planes, the refugees are rescued by the Viroma, a tanker also fleeing the Japanese. Thus begins a terrible ordeal, as the Viroma itself is sunk by the Japanese and the survivors take to open boats. Led by stalwart First Officer Nicholson, they will attempt to flee to safety across the South China Sea, relentlessly pursued by the Japanese and equally at risk from traitors in their midst.
Keywords: World War (1939-1945) -- English Fiction -- Adventure Stories